NUTRITIONAL STATUS AS ASSESSED BY BIOIMPEDANCE SPECTROSCOPY IN HYPOKALEMIC VERSUS NORMOKALEMIC CAPD PATIENTS. - Somchai Yongsiri; Suriya Prongnamjai; Pakapan Dinchuthai; Rachneeporn Cheunsuwan; Jiranuch Thammakumpee; Siriporn Tangjaturonrasami; Nattaphon Annanon (The Korean Society of Nephrology, 2012)
Hypokalemia is a significant problem in CAPD patients. The impact of hypokalemia on treatment outcome was not known. The study objective was to compare the nutritional status as measured by Multifrequency bioimpedance spectroscopy (BIS) and quality of life between peritoneal dialysis patients who has hypokalemia and normokalemia. There were 8 hypokalemic and 18 normokalemic PD patients in this study. BIS were measured by BCM-body composition monitor (Fresenius medical care) device, quality of life was measured by WHOQOL-BREF questionnaire. Levene's Test was used for comparison and p<0.05 was considered as statistically significant. There was no difference in the co-morbidity, dialysis adequacy, blood pressure and food intake between groups. The quality of life between groups was not statistically difference. BIS showed comparable lean tissue index (LTI), fat tissue index (FTI), urea distribution volume and ECW/ICF water ratio. Patients in the normokalemic group had a non-significant higher percent OH/ECW than hypokalemic group. Parameters Hypokalemic Normokalemic p-value Charlson's comorbidity index 8.25+/-2.05 9.06+/-2.54 0.442 Weekly Kt/V 2.06+/-0.35 1.94+/-0.41 0.525 LTI (kg/m2) 11.31+/-5.34 12.51+/-2.68 0.449 FTI (kg/m2) 11.95+/-7.92 10.51+/-4.70 0.567 Urea distribution (L) 28.30+/-8.63 29.64+/-4.92 0.618 ECW/ICW 1.04+/-0.34 1.03+/-0.12 0.909 OH/ECW (%) 13.19+/-13.88 17.71+/-10.04 0.363 In conclusion, nutritional status and quality of life were not statistically different between CAPD patients who had hypokalemia or normokalemia.